Evolutionary Approach to Optimization - Dzidolikaitė, Agnė (Jaunųjų mokslininkų darbai, 2016)
Large amounts of data are used in many science fields. Such data are often visualised to better understand them. There are many multidimensional data visualization methods. One of the best known methods among them is multidimensional scaling. Using this method high dimensional data are visualized into a two or three dimensional space. It is showed in the paper that multidimensional scaling can be used with genetic algorithm to solve optimization problems.